Factors influencing the quality of life among women with cancer in Vietnam - Nguyen, Huyen Thi Hoa; Giap, Tinh Thi Thanh; Tran, Tran Ngoc; Nguyen, Anh Chau; Truong, Trung Quang; Bui, Linh Khanh; Tran Quang, Duc; Anderson, Debra J. (Frontiers in Psychology, 2024)
Background: Cancer and its treatments significantly affect the quality of life (QoL) of patients. This remains understudied among Vietnamese women with cancer.Objectives: This study explored the QoL of Vietnamese women with cancer and identified key influencing factors.In 2022, this study analyzed 214 Vietnamese women with cancer from four hospitals, assessing pain levels (Visualized Pain Scale), functional capacity (Karnofsky Performance Status Scale), and QoL (SF12). Analyses used SPSS 26.0, including t-tests, ANOVA, and hierarchical linear regression models.Results: SF12-PCS and SF12-MCS scores were 46.61 ± 9.70 and 46.96 ± 9.06. Pain score (β = -0.304, p < 0.001) and symptoms number (β = -0.311, p < 0.001) were key predictors of physical health. For mental health, functional status (β = 0.259, p < 0.001) and symptoms number (β = -0.311, p < 0.001) were significant. PCS was negatively correlated with age (r = -0.165, p = 0.016), number of symptoms (r = -0.220, p = 0.001), and pain (r = -0.444, p < 0.001). Mental health (MCS) was negatively correlated with the length of cancer diagnosis (r = -0.156, p = 0.036) and the number of symptoms (r = -0.362, p < 0.001). Both PCS and MCS positively correlated with functional status (r = 0.222, p = 0.001) and (r = 0.281, p < 0.001), respectively.Culturally sensitive care, pain management, and tailored support programs addressing physical, psychological, spiritual, and social aspects can enhance QoL for these women.